(untitled) - Reisberg, Daniel (New York, 2013)
The Cognition Workbook contains engaging essays on research methodology and applications to topics like the legal system and education. Students are offered numerous hands-on activities to try themselves, including demonstrations of articulatory rehearsal loops, common errors in judgment and reasoning, the effect of practice on the cognitive unconscious, and many more. The new edition includes many new essays, activities, and demonstrations that focus on the real-world applications of cognitive psychology, and builds a bridge between the course and students’ own concerns.
Keywords: Cognition,Rối loạn ngôn ngữ,Nhận thức,Language disorders; Problems, exercises, etc.,Bệnh nhân,Phục hồi chức năng,Vấn đề, tập luyện, vv,Patients,Rehabilitation